Aliran Psikoanalisis Dalam Perspektif Islam - Faiqatul Husna (SALAM: Jurnal Sosial dan Budaya Syar-i, 2018)
Abstract: Humans are the most perfect creatures of God among all beings on this earth. Humans have more problems faced by other creatures in living life, both from social contact and so on. Therefore, some of the many people are scientists doing various ways to find solutions to these problems. Finally, psychology was born which discussed the human psyche. Psychology has a variety of sciences. One of them is developmental psychology. Developmental psychology is a branch of psychology that discusses human psychological development from prenatal to near death. On this occasion will examine and understand one of the schools of psychology, namely the flow of psychoanalysis. In addition to studying the scope of psychoanalysis and its relation to Islamic psychology.Keywords: Psychology, Psychoanalysis, Islamic Perspective. Abstrak:Manusia adalah makhluk ciptaan Allah yang paling sempurna di antara seluruh makhluk di muka bumi ini. Manusia memiliki lebih banyak masalah yang dihadapi dibandingkan makhluk lain dalam menjalani kehidupan, baik dari kontak sosial dan lain sebagainya. Maka dari itu, beberapa orang dari sekian banyak manusia itu yakni para ilmuan melakukan berbagai cara untuk mencari pemecahan masalah tersebut. Akhirnya, lahirlah ilmu psikologi yang membahas tentang kejiwaan manusia. Psikologi memiliki berbagai macam ilmu. Salah satu di antaranya adalah psikologi perkembangan. Psikologi perkembangan merupakan suatu cabang ilmu psikologi yang membahas tentang perkembangan kejiwaan manusia dari prenatal sampai hampir meninggal. Pada kesempatan ini akan mengkaji dan memahami salah satu aliran psikologi yaitu aliran psikoanalisis. Selain dikaji ruang lingkup psikoanalisis serta kaitannya dengan psikologi islam.Kata Kunci: Aliran psikologi, Psikoanalisis, Perspektif Islam.